Comparison of Different Subject Cultures and Pedagogical Use of ICTs in Estonian Schools - Agnese Karaseva; Pille Pruulmann-Vengerfeldt; Andra Siibak (Universitetsforlaget, 2013)
This paper explores the ways in which teachers have integrated ICTs in teaching humanities and science classes at the elementary and primary school levels. The research is based in Estonia, looking at five Estonian and one Russian-speaking primary and elementary schools. Data were gathered through classroom observations and two consecutive interviews with 16 teachers. Our findings indicate that technology use is strongly related to the teacher's dominant instructional style and the specific subject culture. Keywords: pedagogic use of ICT, subject cultures, instructional styles, Estonia